Volumetric changes in hippocampal subregions and their relation to memory in pediatric nonlesional localization‐related epilepsy. Issue 4 (11th February 2014) - Widjaja, Elysa; Zamyadi, Mojdeh; Raybaud, Charles; Snead, O. Carter; Smith, Mary Lou
Summary Objective Developmental differences in structure and function have been reported along the hippocampal subregions. The aims of this study were to determine if there were volumetric differences in hippocampal head (HH), body (HB), tail (HT), and total hippocampus (TotH)) in children with nonlesional localization‐related epilepsy relative to controls, and the relation between hippocampal subregions with episodic memory and clinical parameters. Methods Forty‐eight children with nonlesional localization‐related epilepsy, consisting of 29 left‐sided and 19 right‐sided epilepsy, and 27 healthy controls were recruited. All patients and controls underwent volumetric T1‐weighted imaging, and verbal and nonverbal memory testing. The volume of hippocampal subregions was compared between patients and controls. The associations between left hippocampal subregions with verbal memory; right hippocampal subregions with nonverbal memory; and hippocampal subregions with age, age at seizure onset, and seizure frequency were assessed. Results Patients with left‐sided epilepsy had smaller left HH (p = 0.003) and HB (p = 0.012), right HB (p = 0.021) and HT (p = 0.015), and right TotH (p = 0.020) volumes. Those with right‐sided epilepsy had smaller right HT (p = 0.018) volume. There were no statistically significant differences between verbal and nonverbal memory in left‐sided and right‐sided epilepsy relative to controls (all p > 0.025). In left‐sided epilepsy, there was a significant association between left HH volume with verbal memory (β = 0.492, p = 0.001). There was no significant association between left and right hippocampal subregions with verbal and nonverbal memory, respectively, in right‐sided epilepsy and controls (all p > 0.002). In left‐sided and right‐sided epilepsy, there was no significant association between hippocampal subregions with age, age at seizure onset, and seizure frequency (all p > 0.002). Significance We have found hippocampal volume reduction, but did not identify a gradient in the severity of volume reduction along the hippocampal axis in children with localization‐related epilepsy. Further study is needed to clarify if there are volumetric changes within the cornu ammonis subfields and dentate gyrus. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.